Functional Analysis of Two Odorant-Binding Proteins, MaltOBP9 and MaltOBP10, in Monochamus alternatus Hope - Li, Dong-Zhen; Huang, Xiao-Feng; Yang, Rui-Nan; Chen, Jing-Yuan; Wang, Man-Qun (Frontiers in Physiology, 2020)
Odorant-binding proteins (OBPs) are important for the perception of chemical signals by insects. Effective pest management strategies can be developed by understanding the host location mechanism and the physiological functions of OBPs in olfactory detection. In this study, we cloned two OBPs from Monochamus alternatus, where MaltOBP9 was highly expressed in multiple insect tissues and MaltOBP10 was highly expressed in the female antenna according to the results of qRT-PCR. The recombinant proteins were successfully purified in vitro. Immunocytochemistry indicated the high expression of MaltOBP9 and MaltOBP10 in the sensillum lymph of sensilla basiconica, sensilla trichodea, sensilla auricillica, and sensilla chaetica, thereby demonstrating their broad participation in semiochemical detection. Both proteins were localized in the inner cavity of mechanoreceptors and they exhibited broad binding abilities with volatiles from pine bark according to fluorescence competitive binding assays. Due to its broad binding ability and distribution, MaltOBP9 may be involved in various physiological processes as well as olfactory detection. MaltOBP10 appears to play a role in the fundamental olfactory recognition process of female adults according to its broad binding ability. These findings suggest that OBPs may have various physiological functions in insects, thereby providing novel insights into the olfactory receptive mechanism.